I Implementasi Model Observers Laravel Pada Activity Logging Sistem Informasi Penjualan - Usep Abdul Rosid; Chepy Perdana (Jurnal Sistem Informasi Galuh, 2026)
An activity logging component within a sales information system is critical for maintaining data integrity and internal audit accountability. In conventional web application development, developers frequently embed logging scripts directly inside business controllers, which triggers code redundancy and violates the Separation of Concerns (SoC) principle. This study aims to design and implement an automated audit trail component within a sales information system, with a case study conducted at XYZ. The system development follows the Waterfall SDLC methodology, encompassing requirements analysis, system and database design, and code implementation. The implementation results demonstrate that utilizing the booted method within Eloquent models completely isolates the auditing logic from the main business controllers. Furthermore, this research effectively mitigates state management amnesia within user interface pagination by formulating an adaptive routing redirect strategy during data creation. The engineered system successfully records structured log activities detailing user identities, localized timestamps, and comprehensive descriptions of data mutations without relying on any external third-party packages.